Escape mapping to achieve bidirectional block: A case series. Issue 4 (26th November 2018) - Gabriels, James; Beldner, Stuart; Donnelly, Joseph; Willner, Jonathan; Epstein, Laurence M.; Patel, Apoor
Abstract: Escape mapping is a novel technique that can be used to locate sites of persistent conduction and achieve exit block during an atrial fibrillation ablation. This method allows for mapping solely with the ablation catheter in the left atrium by annotating to a catheter in the coronary sinus. We illustrate the utility escape mapping during an atrial fibrillation ablation where entrance block is achieved without exit block. We further expand upon this technique by describing the first reported case of escape mapping being used to achieve bidirectional block during an atrial flutter ablation.